2008
DOI: 10.1128/iai.01162-07
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Pyrogenic Exotoxin B-Induced Apoptosis in A549 Cells Is Mediated through α v β 3 Integrin and Fas

Abstract: Our previous work suggested that streptococcal pyrogenic exotoxin (SPE) B-induced apoptosis is mediated through a receptor-like mechanism. In this study, we have identified ␣ v ␤ 3 and Fas as the SPE B receptors for this function. The SPE B fragment without the RGD motif and G308S, a SPE B mutant with the RSD motif, induced less apoptosis than did native SPE B, suggesting that the RGD motif is critical for SPE B-induced apoptosis. Fluorescein isothiocyanate-SPE B binding assays and immunoprecipitation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…3A), which agreed with our previous report [29]. The reduction of surface α4 integrin could be due to apoptotic cell death, which has been shown to cause integrin endocytosis [36]. Treating the cell with L-NAC (free radical scavenger) or 1400w (iNOS inhibitor) reduced the numbers of cells that contained surface α4 integrin without or with UVB-irradiation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…3A), which agreed with our previous report [29]. The reduction of surface α4 integrin could be due to apoptotic cell death, which has been shown to cause integrin endocytosis [36]. Treating the cell with L-NAC (free radical scavenger) or 1400w (iNOS inhibitor) reduced the numbers of cells that contained surface α4 integrin without or with UVB-irradiation (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Both extrinsic and intrinsic death pathways are involved in the process (8). We have also identified integrin ␣ V ␤ 3 and Fas as receptors for SPE B, which mediates RGD motif-dependent and -independent pathways (20). In the present study we have further identified two of the pathways mediated by integrin ␣ V ␤ 3 and by Fas for increasing the expression of procaspase 8 and Bax.…”
Section: Discussionmentioning
confidence: 50%
“…We have previously identified integrin ␣ V ␤ 3 and Fas as receptors for SPE B-induced apoptosis, mediated by RGD motifdependent and -independent pathways, respectively (20). In the present study we further elucidate the roles of the STAT1 and MAPK pathways in the SPE B-induced apoptotic pathway.…”
mentioning
confidence: 52%
“…Several pathogens, such as Salmonella enterica (42), Streptococcus pyogenes (57), and Helicobacter pylori (55), have been reported to induce apoptosis mediated by Fas. H. pylori can also induce apoptosis through activation of p53 (8).…”
Section: Discussionmentioning
confidence: 99%